ASESMEN DIAGNOSTIK DALAM MATERI DONGENG PADA MATA PELAJARAN BAHASA SUNDA DI KELAS VII SEKOLAH MENENGAH PERTAMA (SMP) YAYASAN WANITA KERETA API (YWKA) BANDUNG - Okke Rosmaladewi; Cucu Amirah; Sandi Sopandi; Kurniawati Kurniawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The purpose of this study was to find out the diagnostic assessment in fairy tale material in Sundanese language subjects. The background of the diagnostic assessment is the change in face-to-face teaching and learning activities to distance learning (PJJ), the decline in the ability of students, the failure to achieve learning objectives and the competency gaps of students. One effort to overcome this problem is to carry out an assessment at the beginning of learning which is called a diagnostic assessment. The approach used in this study uses a quantitative approach with quantitative descriptive methods, meaning that data is collected from instruments in the form of non-cognitive diagnostic assessments of fairy tales and then analyzed based on students' answers to each question, then set forth in tables and diagrams and percentages are taken. The population consists of two classes in class VII with a total of 51 students. a sample of 26 students in class VII. That directly or indirectly the role of parents affects children regarding their likes or dislikes of fairy tales. This role is not only in the form of storytelling for children, but rather encourages children to like reading fairy tale books. When children like fairy tales, this material will be easier to teach because the child's ability to understand is sufficient to explore it. It's different if the child doesn't like fairy tales. The first thing the teacher does for students like this is of course to motivate them to like the material first and the role of parents influences children regarding their likes or dislikes of fairy tales.